2D Inorganic–Antimalarial Drug–Polymer Hybrid with pH‐Responsive Solubility. Issue 10 (17th June 2015) - Kim, Ji‐Yeong; Yang, Jae‐Hun; Lee, Ji‐Hee; Choi, Goeun; Park, Dae‐Hwan; Jo, Mi‐Rea; Choi, Soo‐Jin; Choy, Jin‐Ho
Abstract Artesunic acid (ASH), an antimalarial drug, has low oral bioavailability due to its low aqueous solubility. To overcome this problem, artesunate (AS) was intercalated into zinc basic salt (ZBS) via co‐precipitation. AS was immobilized with a tilted double layer arrangement, which was also confirmed by XRD and 1‐D electron density mapping. In order to decrease the release rate of AS under gastrointestinal conditions and to simultaneously increase the release rate of AS under intestinal conditions, ZBS‐AS was coated with EUDRAGIT L100 (ZBS‐AS‐L100). Finally, we performed an in‐vivo pharmacokinetic study to compare the oral bioavailability of AS of ZBS‐AS‐L100 with that of ASH. Surprisingly, it was found that the former is 5.5 times greater than the latter due to an enhanced solubility of AS thanks to the ternary hybridization with ZBS and EUDRAGIT L100. Therefore, the present ZBS‐AS‐L100 system has a great potential as a novel antimalarial drug formulation with pH selectivity and enhanced bioavailability.